Total synthesis of selaginellin S. Issue 25 (18th June 2020) - Fujiwara, Kenshu; Itagaki, Takaya; Kondo, Yoshihiko; Akiba, Uichi; Tokiwano, Tetsuo
Graphical abstract: Highlights: Successful total synthesis of selaginellin S. A strategy based on Diels-Alder reaction followed by dehydrogenative aromatization. The structure of selaginellin S was confirmed by the present total synthesis. Selaginellin S is suggested to have no axial chirality at ambient temperature. Abstract: The total synthesis of selaginellin S, isolated from Selaginella pulvinata, was achieved via a concise route including Diels-Alder reaction and dehydrogenative aromatization. The NMR analysis of the synthetic compound confirmed the structure of natural selaginellin S. Although the natural compound was reported to have an axial chirality, the absence of the axial chirality of selaginellin S at ambient temperature was suggested from lineshape changes in variable temperature NMR experiments with the pivaloyl derivative of the synthetic compound.